Urgensi Penafsiran Saintifik Al-Qur’an: Tinjauan atas Pemikiran Zaghlul Raghib Muhammad al-Najjar - Intan Pratiwi Mustikasari (Studia Quranika, 2021)
This article aims to elaborate the views Zaghlul Raghib Muhammad An-Najjar on the urgency of scientific interpretation of the Qur'an in order to preach the spread of Islam in the modern era. This becomes attractive because in the midst of the pro and contra of tafsir ilmy among the opinions of scholars and mufassir,. Al-Najjar seeks to corroborate the evidence of the urgency of scientific interpretation in his book "Tafsīr al-Âyāt al-Kauniyah Fī al-Qur'ān Al-Karīm" which provides amazing and accurate information about the nature of the universe and its phenomena in which applied science that has not reached the fact except after centuries of revelation of the Qur'an. The finding shows Zaghlul al-Najjar stated that the scientific interpretation has a great role to prove and to explain the side of scientific miracles of the Quran in the middle of modern society by not ruling out the perspective of classical interpretation tradition. Moreover. It contains modern scientific facts in discussing kauniyah verses as proof of the truth of the Qur'an as a holy book. Although, with the terms and limitations that need to be required an interpretation with a scientific approach in order to avoid unwanted mistakes.